1985
DOI: 10.1016/0032-3861(85)90090-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation phenomena in solutions of polysulfone in mixtures of a solvent and a nonsolvent: relationship with membrane formation

Abstract: The phase separation phenomena in ternary solutions of polysulfone (PSI) in mixtures of a solvent and a nonsolvent (N,N-dimethylacetamide (DMAc) and water, in most cases) are investigated. The liquid-liquid demixing gap is determined and it is shown that its location in the ternary phase diagram is mainly determined by the PSf-nonsolvent interaction parameter. The critical point in the PSf/DMAc/water system lies at a high polymer concentration of about 8~o by weight. Calorimetric measurements with very concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(145 citation statements)
references
References 8 publications
8
135
0
1
Order By: Relevance
“…It has been hypothesized that the denser skin layer and the more porous sublayer are formed by two separate mechanisms [23]. For the top skin layer, the structure is primarily determined by the order of events during phase separation [37].…”
Section: Role Of Solvent-polymer Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been hypothesized that the denser skin layer and the more porous sublayer are formed by two separate mechanisms [23]. For the top skin layer, the structure is primarily determined by the order of events during phase separation [37].…”
Section: Role Of Solvent-polymer Interactionmentioning
confidence: 99%
“…The solutions were stirred while pure nonsolvent (DI water) was added until the polymer solution became irreversibly turbid as determined by visual detection. The cloud point was calculated as the mass ratio of nonsolvent to total polymer solution plus the nonsolvent [23].…”
Section: Determination Of the Cloud Pointmentioning
confidence: 99%
“…They found that the increase of CBT causes the formation of macrovoids and a more porous structure. The coagulation medium is another important synthesis parameter which can exert drastic effects on the resulting structures of membranes made by phase inversion processes (Banks and Sharples, 1966;Saler et al, 1974;Strathmann, 1985;Mulder et al, 1985;Wijmans et al, 1985;Bottmo et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Polysulfone (PSF) and polyethersulfone (PES) have been used by many researchers [1][2][3][4][5][6][7] in the preparation of hollow fiber membranes as membrane forming normally a homogeneous solution, which is forced to phase separate by changing its composition when immersed in a nonsolvent bath. Kinetic processes play a key role in this transition.…”
Section: Introductionmentioning
confidence: 99%